2018
DOI: 10.5650/jos.ess18116
|View full text |Cite
|
Sign up to set email alerts
|

Application of Glycolipid Biosurfactants as Surface Modifiers in Bioplastics

Abstract: INTRODUCTION Biosurfactants BSs are functional amphiphilic compounds produced by a variety of microorganisms. Compared to chemically synthesized surfactants, BSs are more eco-friendly, biocompatible, and multifunctional. Glycolipid-type BSs are the most promising BSs for many industrial processes because of their availability from renewable resources, such as vegetable oils and sugars, and their versatile interfacial and biochemical properties 1, 2. Sophorolipids SL are a class of glycolipid-type BSs that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Kiss et al using Pluronic surfactants [ 17 , 18 ] found differences in water contact angle between 40° and 10° for PLA films without and with surfactants. Similar results were found by many other researchers working with different surfactants, such as Fukuoka et al [ 19 ] or Gifu et al [ 20 ] among others [ 17 , 21 ]. However, Gromer et al [ 22 ], studying the surfactant distribution in films made from polymeric colloids, have shown that there are a large number of factors affecting the surfactant content along the film thickness, such as the type of surfactant and its initial concentration, the inorganic particles present, the size, shape, and thickness of the film, the aging conditions, and even the substrate on which the film is poured.…”
Section: Introductionsupporting
confidence: 90%
“…Kiss et al using Pluronic surfactants [ 17 , 18 ] found differences in water contact angle between 40° and 10° for PLA films without and with surfactants. Similar results were found by many other researchers working with different surfactants, such as Fukuoka et al [ 19 ] or Gifu et al [ 20 ] among others [ 17 , 21 ]. However, Gromer et al [ 22 ], studying the surfactant distribution in films made from polymeric colloids, have shown that there are a large number of factors affecting the surfactant content along the film thickness, such as the type of surfactant and its initial concentration, the inorganic particles present, the size, shape, and thickness of the film, the aging conditions, and even the substrate on which the film is poured.…”
Section: Introductionsupporting
confidence: 90%
“…They show for example interesting self-assembling properties and phasebehavior (Worakitkanchanakul et al, 2009;Fukuoka et al, 2012), cell-differentiation activity (Isoda et al, 1997) and interaction with proteins (Konishi et al, 2007). They have also been reported to be valuable ingredients for hair and skin care products (Morita et al, 2010;Yamamoto et al, 2012), for agro-chemicals (Fukuoka et al, 2015), and they could be used as surface-modifiers in bioplastics (Fukuoka et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Sodium salts improves the aqueous solubility of CLs and favours the formation of gels in alcoholic solution (ethanol or 1,3-butanediol) [ 119 , 120 ]. CL from C. humicola , when added to poly (lactic acid) films, modifies the surface properties increasing, for example, its wettability [ 121 ].…”
Section: Structural Classes Properties and Applicationsmentioning
confidence: 99%